Hardware in the Loop Test-Rig for Identification and Control Application on High Speed Pantographs. (2004) - Collina, A.; Facchinetti, A.; Fossati, F.; Resta, F.
Abstract : Trains current collection for traction motors is obtained by means of a sliding contact between the overhead line (OHL) and the collector strips mounted on the pantograph head. The normal force by which the collector presses against the contact wire ensures the contact pressure for the electrical contact. As the train speed increases, the variation of contact force between pantograph and catenary increases, and the pantograph-OHL dynamic interaction becomes greater. This condition causes excessive mechanical wear and contact wire uplift (for high values of contact forces), and leads to high percentage of contact loss, arcing and electrically related wear. The topic of actively controlled pantograph is gaining more interest as a tool to increase the performance of the current collection at high speed. In the last few years, it appears possible to transfer the knowledge based on numerical experiments, to the real operating condition. An important step in this direction is the set up of a laboratory hardware in the loop test-rig in which the control strategies and the actuation can be tested, before tests performing in real life conditions, in order to demonstrate their actual feasibility. The present paper describes an hardware in the loop (HIL) test-rig developed by the authors, which allows to reproduce the dynamical interaction between overhead lines and pantograph in high speed railways. Using the described laboratory set-up, experimental investigation on the problems related with pantograph-OHL interaction can be performed, very similarly to the real life operating conditions, with the advantage of varying test parameters and conditions easily.